Conservation of dark CPD photolyase function in blind cavefish - Hongxiang Li; Carina Scheitle; Giuseppe Di Mauro; Silvia Fuselli; Susanne Fritsch-Decker; Takeshi Todo; Carsten Weiss; Daniela Vallone; Tilman Lamparter; Cristiano Bertolucci; Nicholas S. Foulkes (Nature Communications)
Abstract DNA damage is generated by various environmental stressors and so DNA repair systems must inevitably adapt to changing environments. Photolyases represent a highly conserved class of enzymes which repair UV-induced covalent crosslinks between adjacent pyrimidine bases (CPD and 6-4 photoproducts) via photoreactivation. In the blind cavefish Phreatichthys andruzzii which has evolved for millions of years completely isolated from UV radiation and visible light, we have documented multiple polymorphisms and loss of function mutations affecting both the 6-4phr and DASHphr photolyase genes while strangely, the CPDphr gene remains highly conserved. Using loss and gain of photolyase function medaka and mammalian cell lines, we reveal a novel function for CPDphr. Specifically, it enables the light-independent repair of CPD as well as 8-OHdG, an oxidatively modified form of guanosine which are both generated under oxidative stress in the absence of UV radiation. Thereby we document selective conservation of light-independent photolyase function in blind cavefish, enabling the repair of DNA damage encountered in an extreme subterranean environment.